Effect of dexmedetomidine on acute lung injury in experimental ischemia-reperfusion model - Küçükebe,Ömer Burak (2017)
Abstract Purpose: Ischemia-reperfusion injury is one of the consequences of tourniquet application for extremity surgery. The aim of the study was to establish the effect of dexmedetomidine on the acute lung injury following lower extremity experimental ischemia-reperfusion model in rats. Methods: Twenty-eight Wistar-Albino breed Rats were recruited after Ethics Committee approval and allocated into 4 groups, each with 7 subjects. Group 1 (SHAM) received only anesthesia. Group 2 (IR) had experienced 3 h of ischemia and 3 h of reperfusion using left lower extremity tourniquet after anesthesia application. Groups 3 (D-50) and 4 (D-100) had undergone the same procedures as in the Group 2, except for receiving 50 and 100 mg·kg-1, respectively, dexmedetomidine intraperitoneally 1 h before the tourniquet release. Blood samples were obtained for the analysis of tumor necrosing factor-α and interleukin-6. Pulmonary tissue samples were obtained for histological analysis. Results: No significant difference regarding blood tumor necrosing factor-α and interleukin-6 values was found among the groups, whereas pulmonary tissue injury scores revealed significant difference. Histological scores obtained from the Group 2 were significantly higher from those in the Groups 1, 3 and 4 with p-values 0.001 for each comparison. Moreover, Group 1 scores were found to be significantly lower than those in the Groups 3 and 4 with p-values 0.001 and 0.011, respectively. No significant difference was observed between the Groups 3 and 4. Conclusion: Dexmedetomidine is effective in reduction of the experimental ischemia-reperfusion induced pulmonary tissue injury in rats, formed by extremity tourniquet application.